1980
DOI: 10.1007/bf00561587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posture and sleep on pharmacokinetics

Abstract: The pharmacokinetics of amoxycillin in normal male volunteers was studied during the states of bedrest, sleep and ambulation. The absorption and disposition of amoxycillin in ambulatory subjects was found to be comparable to that reported previously by other workers. Serum amoxycillin concentrations were found to be significantly greater during ambulation than during bedrest and sleep. The difference in serum levels resulted from an increased apparent total serum clearance and amoxycillin renal clearance durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…As shown in Table 2, several studies, for example, with paracetamol [18,20,21], nifedipine [18], amoxycillin [22] and theophylline [23], have found an increase in the time to reach the maximum serum drug concentration (t max )/mean residence time (MRT) and/or a decrease in maximum plasma drug concentration (C max )/ (early) AUC for left lateral and supine position compared to other positions (right lateral, prone, sitting, standing). The effects of the respective postures on pharmacokinetics correspond to their effects on gastric emptying, as discussed above (left lateral and supine positions tend to decrease the rate of gastric emptying).…”
Section: Effects Of Posture On the Absorption Of Orally Administered mentioning
confidence: 99%
“…As shown in Table 2, several studies, for example, with paracetamol [18,20,21], nifedipine [18], amoxycillin [22] and theophylline [23], have found an increase in the time to reach the maximum serum drug concentration (t max )/mean residence time (MRT) and/or a decrease in maximum plasma drug concentration (C max )/ (early) AUC for left lateral and supine position compared to other positions (right lateral, prone, sitting, standing). The effects of the respective postures on pharmacokinetics correspond to their effects on gastric emptying, as discussed above (left lateral and supine positions tend to decrease the rate of gastric emptying).…”
Section: Effects Of Posture On the Absorption Of Orally Administered mentioning
confidence: 99%
“…Thus, the distribution of several drugs, is changed not only by several types of stress (Swartz & Sidell, 1973;Chapman et al, 1948), but also by a change in posture intermediate between the supine and standing position in resting subjects. Higher initial plasma concentrations and a more rapid initial disappearance rate suggest an altered distribution from a contracted central compartment, to an expanded peripheral compartment as indicated by studies with amoxycillin given orally (Roberts & Denton, 1980) and benzyl penicillin given intramuscularly (Levy, 1967).…”
Section: Resultsmentioning
confidence: 99%
“…Interest in the effect of posture on pharmacokinetics in man has centred mainly on the difference between supine rest and ambulation (Levy, 1967;Roberts & Denton, 1980;Swartz & Sidell, 1973;Swartz et al, 1974). In these studies postural changes in elimination kinetics were observed with high clearance drugs, and were related to concomitant changes in blood plasma flow of the eliminating organ.…”
Section: Introductionmentioning
confidence: 99%
“…Standing and exercising, by lowering renal perfusion, reduce the clearance of renally excreted drugs (Roberts & Denton, 1980;Mason et al, 1980). This phenomenon could be more important in patients known to have lower baseline renal perfusion (elderly, severe hypertensives, patients with renal insufficiency), who may further be disadvantaged.from the reduction of renal flow caused by drugs like propranolol.…”
Section: Discussionmentioning
confidence: 99%